مساهمة صندوق النقد العربي في تمويل التجارة الخارجية العربية - عمر, لعبيني; سميحة, بن محياوي (Sciences humaines; Vol. 33 (2014): SCIENCES HUMAINES)
تشهد الدول العربية تحديات إستراتيجية        و تغيرات متسارعة في أنظمتها الاقتصادية والتجارية ، وزيادة تأثير وتأثر هذه الاقتصاديات بالتطورات الاقتصادية العالمية     و اندماجها في التجارة الدولية ، بحيث أصبحت الدول العربية أكثر اعتمادا وانكشافا على العالم الخارجي .       وعليه قامت الدول العربية بتأسيس مؤسسات مالية عربية إقليمية كان أهمها صندوق النقد العربي الذي يهدف إلى مساعدة الدول العربية في مجابهة الآثار السلبية التي يفرزها التغير السريع الحاصل في الاقتصاد العالمي و كذلك لتدعيم جهوده االرامية للإصلاح والتكيف ودعم برامج التنمية، حيث قام صندوق النقد العربي بدعم تطبيق سياسات دمج التجارة الخارجية فيخطط وبرامج التنمية للدول الأعضاء و تنمية المبادلات التجارية الخارجية، وذلك عن طريق تقديم التمويل اللازم للعمليات التجارية الخارجية و استغلال الفرص التجارية في الأسواق العالمية وتعظيم استفادة الاقتصاديات العربية من مشاركتها في النظام التجاري العالمي.   Abstract :   Arab states are experiencing strategicchallenges and rapid changes in their economic and commercial systems,as well as the increase of impact and effect of these economies by global economic developments and their integration into international trade, so that Arab countries have become more dependentand vulnerable to the outside world. Accordingly, the Arab countries have establisheddifferent regional financial institutions; the most important was the Arab Monetary Fund, which aims to help Arab countries in confronting the negative effects issued by the rapid change taking place in the global economy, as well asto strengthen their efforts to reform, adjustment and supporting development programs. TheArab Monetary Fundundertook the support of application of integration policies of foreign trade in the development plans and programs of the Member States, and the development of foreign trade; by providing the necessary funds for the operations of foreign trade and by the exploitation of business opportunities in the global markets and maximizing the benefit of Arab economies to participation in the global trading system.